Carbon felt electrode material loaded with copper-containing oxide as well as preparation method and application of carbon felt electrode material
Through the carbon felt electrode material loaded with copper oxide, the problem of poor electrocatalytic degradation of dye wastewater is solved, and efficient degradation of high-concentration methylene blue wastewater is achieved, cost reduction and promotion and application of technology is promoted.
Patent Information
- Application Number
- CN202411870057.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-18
- Publication Date
- 2025-02-28
- Estimated Expiration
- Not applicable · inactive patent
Smart Images

Figure CN119528281A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of wastewater treatment, and in particular to a carbon felt electrode material loaded with copper oxide, and a preparation method and application thereof. Background Art
[0002] With the development of dye production and printing and dyeing industry, the discharge of dye industry wastewater has also increased dramatically. Dye wastewater has the characteristics of high chromaticity, high content of organic pollutants, complex composition, large water quality changes, high biological toxicity, etc., which makes it difficult to degrade and treat. Printing and dyeing wastewater contains a large amount of organic pollutants. Discharge into the water body will consume dissolved oxygen, destroy the ecological balance of water, and endanger the survival of fish and other aquatic organisms. Organic matter that sinks to the bottom of the water will produce harmful gases such as hydrogen sulfide due to anaerobic decomposition, and deteriorate the environment.
[0003] With the development of science and technology, electrocatalytic degradation of dye wastewater, including methylene blue wastewater, has become a common treatment method. Electrocatalytic degradation of dye wastewater is to apply an electric field to the dye wastewater, and a series of chemical reactions occur under the power. The electrochemical reaction is carried out in the electrochemical reactor, and a large number of highly oxidizing free radicals are produced to effectively degrade the dye pollutants. Among them, the properties of the electrode material have a great influence on the electrochemical reaction. When electrochemical oxidation occurs, the anode not only affects the reaction process of electrochemical oxidation, but also affects the reaction efficiency.
[0004] There are many types of common electrode materials, such as metal electrodes including platinum and carbon electrodes made of carbon materials. Although these electrode materials can have an electrocatalytic degradation effect on dye wastewater, the effect of electrocatalytic degradation is limited. For example, the degradation rate of methylene blue wastewater is not high, especially for high-concentration methylene blue wastewater with an initial concentration greater than 10ppm, it is difficult to achieve effective degradation. Summary of the invention
[0005] The purpose of the present invention is to overcome the deficiencies of the prior art and provide a carbon felt electrode material loaded with copper oxide and a preparation method and application thereof, thereby solving the technical problem that the current electrode material has a poor electrocatalytic degradation effect on dye wastewater.
[0006] In order to achieve the above object, the present invention adopts the following technical solutions:
[0007] The present invention provides a method for preparing a copper oxide-loaded carbon felt electrode material, comprising the following steps:
[0008] The carbon felt electrode material loaded with amidoxime groups is subjected to a hydrolysis reaction in an alkaline solution, and the nitrile group of polyacrylonitrile is hydrolyzed into amide groups and carboxyl groups, so as to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups; the modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups is used as a working electrode, and a double electrode system is adopted to perform an electrodeposition treatment on copper-containing wastewater, and copper is oxidized into copper-containing oxides, so as to obtain a copper-containing carbon felt electrode material; the copper-containing carbon felt electrode material is subjected to an oxidation reaction, so as to obtain a carbon felt electrode material loaded with copper-containing oxides; wherein the copper-containing oxide is a mixture of cuprous oxide and cupric oxide.
[0009] The preparation method of the present invention performs alkaline hydrolysis on a carbon felt electrode material loaded with amidoxime to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups, and uses the modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups to electro-deposit copper-containing wastewater to obtain a copper-containing carbon felt electrode material, and finally utilizes oxidation of the copper-containing carbon felt electrode material to obtain a carbon felt electrode material loaded with copper oxides, thereby achieving the combination of copper oxides and carbon felt, enhancing the electrocatalytic degradation ability of the electrode material, and preparing an electrode material with good electrocatalytic degradation effect on dye wastewater, thereby solving the technical problem that the current electrode material has poor electrocatalytic degradation effect on dye wastewater.
[0010] Optionally, the alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkaline solution is 0.5 mol / L to 1.5 mol / L.
[0011] Optionally, the reaction temperature of the hydrolysis reaction is 50°C to 70°C, and the reaction time is 10min to 20min.
[0012] Optionally, the method for preparing the amidoxime-loaded carbon felt electrode material comprises the following steps:
[0013] The carbon felt is immersed in a polyacrylonitrile solution and subjected to ultrasonic treatment so that the polyacrylonitrile is uniformly loaded on the carbon felt, thereby obtaining the carbon felt loaded with polyacrylonitrile;
[0014] The carbon felt loaded with polyacrylonitrile is immersed in a hydroxylamine hydrochloride-sodium carbonate solution to make polyacrylonitrile and hydroxylamine hydrochloride undergo amidoxime reaction, thereby obtaining the carbon felt electrode material loaded with amidoxime.
[0015] It should be noted that in actual operation, only part of the nitrile groups in polyacrylonitrile undergo amidoxime reaction with hydroxylamine hydrochloride and are converted into amidoxime groups. When the carbon felt electrode material loaded with amidoxime groups undergoes hydrolysis reaction in an alkaline solution, the nitrile groups that have not undergone amidoxime reaction are converted into amide groups and carboxyl groups, thereby obtaining a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups at the same time. Since amidoxime groups, amide groups and carboxyl groups are all active for Cu 2+Compared with the carbon felt electrode material loaded with amidoxime groups, the modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups has a better adsorption effect during the electrodeposition process. 2+ The adsorption sites of the modified carbon felt electrode materials containing amidoxime, amide and carboxyl groups are significantly increased. 2+ The electrodeposition effect is better.
[0016] Optionally, the polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in N,N-dimethylformamide, and the mass concentration of the polyacrylonitrile solution is 0.04 g / mL to 0.06 g / mL.
[0017] Optionally, the hydroxylamine hydrochloride-sodium carbonate solution is prepared by dissolving hydroxylamine hydrochloride and sodium carbonate in water, wherein the mass ratio of the hydroxylamine hydrochloride to the sodium carbonate is 1:1, and the mass concentrations of the hydroxylamine hydrochloride and the sodium carbonate in the hydroxylamine hydrochloride-sodium carbonate solution are 0.03 g / mL to 0.05 g / mL.
[0018] Optionally, the temperature of the oxidation reaction is 500° C. to 600° C., and the reaction time of the oxidation reaction is 3 min to 7 min.
[0019] Optionally, the metal element in the copper-containing wastewater is copper.
[0020] Optionally, when the copper-containing wastewater is subjected to the electroplating treatment, direct current or asymmetric alternating current is used, and the electroplating treatment time is 1 hour to 3 hours. Wherein, when the asymmetric alternating current is used, the frequency of the asymmetric alternating current is 400 Hz, the high potential of the asymmetric alternating current is +3V to +7V, accounting for 10% to 30% of the time, and the low potential is -10V to -3V, accounting for 70% to 90% of the time.
[0021] The present invention also provides a carbon felt electrode material loaded with copper oxide, and the carbon felt electrode material is prepared by the above-mentioned preparation method.
[0022] The present invention also provides an application of the copper oxide-loaded carbon felt electrode material as an electrode in degrading dye wastewater.
[0023] The specific application methods are as follows:
[0024] The carbon felt electrode material loaded with copper oxide was made into a working electrode, and a double electrode system was used to electrocatalyze the degradation of dye wastewater. In the double electrode system, the working electrode was used as the anode, the platinum electrode was used as the cathode, the sodium sulfate solution was used as the electrolyte, and direct current was used with a voltage of 10V.
[0025] Compared with the prior art, the present invention has the following beneficial effects:
[0026] 1. The preparation method of the present invention obtains a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups by alkaline hydrolysis of a carbon felt electrode material loaded with amidoxime, and obtains a copper-containing carbon felt electrode material by treating copper-containing wastewater with the modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups through electrodeposition. Finally, the copper-containing carbon felt electrode material is oxidized to obtain a carbon felt electrode material loaded with copper oxides, thereby achieving a combination of copper oxides and carbon felt, enhancing the electrocatalytic degradation ability of the electrode material, and preparing an electrode material with better electrocatalytic degradation effect on dye wastewater, thereby solving the technical problem that the current electrode material has poor electrocatalytic degradation effect on dye wastewater.
[0027] 2. The present invention also obtains the copper element required in the copper-containing oxide by electroplating the copper-containing wastewater, thereby reducing the cost of obtaining the copper element, thereby reducing the preparation cost of the carbon felt electrode material loaded with copper oxide, and facilitating the promotion and application of the carbon felt electrode material loaded with copper oxide in the electrocatalytic degradation of dye wastewater.
[0028] 3. The present invention performs alkaline hydrolysis on the carbon felt electrode material loaded with amidoxime to obtain the modified carbon felt electrode material containing amidoxime group, amide group and carboxyl group, which increases the adsorption sites of copper ions during the electrodeposition treatment process, thereby improving the recovery rate of copper element in copper-containing wastewater, further reducing the preparation cost of the carbon felt electrode material loaded with copper oxide, and facilitating the promotion and application of the carbon felt electrode material loaded with copper oxide in the electrocatalytic degradation of dye wastewater. BRIEF DESCRIPTION OF THE DRAWINGS
[0029] Figure 1 The present invention provides a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 at different magnifications. a is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; b is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; c is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; d is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm.
[0030] Figure 2 This is an XRD image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 provided by the present invention.
[0031] Figure 3 This is an EDS image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 provided by the present invention.
[0032] Figure 4 The present invention provides Cu 2+The test data statistics of the electrodeposition effect comparison experiment. (a) is the effect of different working electrodes on Cu at different time points. 2+ (a) is a comparative statistical chart of the electrodeposition recovery rates of different working electrodes for Cu2+; (b) is a comparative statistical chart of the maximum electrodeposition recovery rates of different working electrodes for Cu2+.
[0033] Figure 5 The present invention provides a statistical graph of test data of a comparative experiment on the electrocatalytic degradation of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages. (a) is a statistical comparison of the degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages at different time points; (b) is a statistical comparison of the maximum degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages.
[0034] Figure 6 The present invention provides a statistical graph of test data of a comparative experiment on the electrocatalytic degradation of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations. (a) is a statistical comparison graph of the degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations at different time points; (b) is a statistical comparison graph of the maximum degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations. DETAILED DESCRIPTION
[0035] In order to make the purpose, technical solution and advantages of the present invention more clearly understood, the present invention is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.
[0036] Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in the field without making any creative work shall fall within the scope of protection of the present invention.
[0037] Although existing electrode materials can play an electrocatalytic degradation effect on dye wastewater, the effect of electrocatalytic degradation is limited. For example, the degradation rate of methylene blue wastewater is not high, especially high-concentration methylene blue wastewater with an initial concentration greater than 10ppm is difficult to effectively degrade.
[0038] For example, a document entitled "Study on Preparation, Modification and Degradation Performance of Cotton Stalk Carbon Fiber Electrode" discloses a method for preparing cotton stalk carbon fiber, using cotton pulp viscose felt as raw material, and preparing finished cotton stalk carbon fiber after pretreatment, carbonization and activation steps. With cotton stalk carbon fiber as anode, stainless steel as cathode and sodium sulfate as reaction electrolyte, methylene blue solution is electrolyzed in a double electrode system. When the electrolysis voltage is 6V to 15V, the removal rate of methylene blue in a 25mg / L methylene blue solution can only reach about 50%. When the electrolysis voltage is 12V, the removal rate of methylene blue in a 50mg / L methylene blue solution drops to about 35%. Obviously, the effect of the cotton stalk carbon fiber on the electrocatalytic degradation of methylene blue solution is relatively limited, especially the degradation effect of high-concentration methylene blue wastewater with an initial concentration greater than 10ppm is very unsatisfactory.
[0039] In order to solve the above technical problems, the present invention provides a carbon felt electrode material loaded with copper oxide and a preparation method and application thereof. The technical scheme and embodiments of the present invention are now described in detail in conjunction with the accompanying drawings.
[0040] The present invention provides a method for preparing a copper oxide-loaded carbon felt electrode material, comprising the following steps:
[0041] The carbon felt electrode material loaded with amidoxime groups is subjected to a hydrolysis reaction in an alkaline solution to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups; the modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups is used as a working electrode, and a double electrode system is used to perform an electrodeposition treatment on copper-containing wastewater to obtain a copper-containing carbon felt electrode material; the copper-containing carbon felt electrode material is subjected to an oxidation reaction to obtain a carbon felt electrode material loaded with copper-containing oxides; wherein the copper-containing oxides are a mixture of cuprous oxide and cupric oxide, and the concentration of the alkaline solution is 0.5 mol / L to 1.5 mol / L.
[0042] Subsequent experimental results show that for methylene blue solutions with an initial concentration of 100ppm, the degradation rate of methylene blue reaches about 60% when the carbon felt electrode material loaded with copper oxide is used as the working electrode, the electrolysis voltage is 10V, and the reaction time is 60min. For methylene blue solutions with initial concentrations of 80ppm, 60ppm, 40ppm, 20ppm, and 10ppm, the degradation rate of methylene blue can reach more than 60% when the carbon felt electrode material loaded with copper oxide is used as the working electrode, the electrolysis voltage is 10V, and the reaction time is 60min. Among them, when the initial concentration of methylene blue is 10ppm, the degradation rate of methylene blue electrocatalytically degraded by the carbon felt electrode material loaded with copper oxide is optimal, and the degradation rate is greater than 90%.
[0043] The above experimental results indicate that the copper oxide-loaded carbon felt electrode material prepared by the preparation method of the present invention can have a good electrocatalytic degradation effect on the methylene blue solution, especially on high-concentration methylene blue wastewater with an initial concentration greater than 10 ppm. It can still have a good electrocatalytic degradation effect, thereby solving the technical problem that the current electrode material has a poor electrocatalytic degradation effect on dye wastewater.
[0044] The present invention is described in detail below through specific examples. The examples are exemplary and intended to be used to explain the present invention, but should not be understood as limiting the present invention.
[0045] In the following examples, the methods described are conventional methods unless otherwise specified; the reagents and materials described are commercially available unless otherwise specified.
[0046] Example 1
[0047] A method for preparing a carbon felt electrode material loaded with copper oxide comprises the following steps:
[0048] Step 1, preparing a carbon felt electrode material loaded with amidoxime.
[0049] Step 1.1, first cut the carbon felt into 3cm×3cm square pieces, use deionized water to ultrasonically clean the cut carbon felt for 10 minutes to remove soluble impurities on the surface of the carbon felt, use 2% dilute nitric acid to ultrasonically clean the carbon felt for 10 minutes to remove oxides on the surface of the carbon felt, use deionized water to ultrasonically clean the carbon felt again for 10 minutes to remove residual dilute nitric acid, then use anhydrous ethanol to ultrasonically clean the carbon felt for 10 minutes to remove organic impurities on the surface of the carbon felt, then use deionized water to ultrasonically clean the carbon felt for 10 minutes, and then put it into an oven at 60°C to thoroughly dry the carbon felt to prepare bare carbon felt.
[0050] Step 1.2, mix 10g of polyacrylonitrile powder and 200mL of N,N-dimethylformamide, stir for 24h to obtain a polyacrylonitrile coating liquid, immerse the bare carbon felt obtained in step 1.1 in the coating liquid, ultrasonicate for 10min, so that the coating liquid is evenly coated on the surface of the carbon felt. After coating, put it into an oven at 60°C and dry it for 12h to obtain a carbon felt loaded with polyacrylonitrile.
[0051] Step 1.3, measure 150mL of deionized water, weigh 3g of hydroxylamine hydrochloride and 3g of sodium carbonate, mix and dissolve hydroxylamine hydrochloride and sodium carbonate in 150ml of deionized water to obtain a mixed solution. Immerse the carbon felt loaded with polyacrylonitrile obtained in step 1.2 in the mixed solution, heat it in a water bath at 60°C, and react for 2h to make the nitrile group on the surface of the carbon felt loaded with polyacrylonitrile undergo amidoximation reaction. After the reaction, wash the carbon felt with deionized water for multiple times to remove the impurity ions remaining on the surface of the carbon felt, put the cleaned carbon felt into an oven, the oven temperature is 60°C, and the drying time is 12h. After drying, the carbon felt electrode material loaded with amidoxime is obtained.
[0052] Step 2, preparing a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups.
[0053] Step 2.1, measure 200 mL of deionized water, weigh 8 g of sodium hydroxide and dissolve it in 200 mL of deionized water to prepare a sodium hydroxide solution.
[0054] Step 2.2, immersing the carbon felt electrode material loaded with amidoxime in a sodium hydroxide solution, heating in a water bath at 60°C for 15 minutes, and allowing the nitrile groups on the surface of the carbon felt to undergo alkaline hydrolysis. After the reaction, the carbon felt is washed multiple times with deionized water to remove residual impurity ions on the surface of the carbon felt. The washed carbon felt is placed in an oven at 60°C for 12 hours to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups, and carboxyl groups.
[0055] Step 3, preparing a carbon felt electrode material loaded with copper oxide.
[0056] Step 3.1, measure 50mL of Cu 2+ A CuSO4 solution with a concentration of 100 ppm was prepared by adjusting the pH to 3.5 using dilute sulfuric acid to prepare simulated copper-containing wastewater.
[0057] In step 3.2, asymmetric alternating current is used with a frequency of 400 Hz, a high potential of +5 V for 20% of the time, and a low potential of -10 V for 80% of the time. The modified carbon felt electrode material containing amidoxime, amide and carboxyl groups obtained in step 2.2 is made into a cathode electrode, and the carbon felt electrode is used as a counter electrode. The simulated copper-containing wastewater obtained in step 3.1 is subjected to electrodeposition treatment with a reaction time of 180 minutes to obtain a loaded copper-containing carbon felt electrode material.
[0058] Step 3.3, using deionized water to wash the copper-containing carbon felt electrode material obtained in step 3.2 for multiple times to remove impurity ions, after washing, using a box-type resistance furnace for high-temperature oxidation, the box-type resistance furnace temperature is 600°C, the oxidation time is 5 minutes, and after cooling to room temperature, a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups is prepared as a cathode electrode, and a double electrode system is used to perform electrodeposition treatment on copper-containing wastewater to obtain a carbon felt electrode material loaded with copper oxide. Wherein, the copper-containing oxide is a mixture of copper oxide and cuprous oxide.
[0059] Comparative Example 1
[0060] A method for preparing a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups comprises the following steps:
[0061] Step 1, preparing a carbon felt electrode material loaded with amidoxime.
[0062] Step 1.1, first cut the carbon felt into 3cm×3cm square pieces, use deionized water to ultrasonically clean the cut carbon felt for 10 minutes to remove soluble impurities on the surface of the carbon felt, use 2% dilute nitric acid to ultrasonically clean the carbon felt for 10 minutes to remove oxides on the surface of the carbon felt, use deionized water to ultrasonically clean the carbon felt again for 10 minutes to remove residual dilute nitric acid, then use anhydrous ethanol to ultrasonically clean the carbon felt for 10 minutes to remove organic impurities on the surface of the carbon felt, then use deionized water to ultrasonically clean the carbon felt for 10 minutes, and then put it into an oven at 60°C to thoroughly dry the carbon felt to prepare bare carbon felt.
[0063] Step 1.2, mix 10g of polyacrylonitrile powder and 200mL of N,N-dimethylformamide, stir for 24h to obtain a polyacrylonitrile coating liquid, immerse the bare carbon felt obtained in step 1.1 in the coating liquid, ultrasonicate for 10min, so that the coating liquid is evenly coated on the surface of the carbon felt. After coating, put it into an oven at 60°C and dry it for 12h to obtain a carbon felt loaded with polyacrylonitrile.
[0064] Step 1.3, measure 150mL of deionized water, weigh 3g of hydroxylamine hydrochloride and 3g of sodium carbonate, mix and dissolve hydroxylamine hydrochloride and sodium carbonate in 150ml of deionized water to obtain a mixed solution. Immerse the carbon felt loaded with polyacrylonitrile obtained in step 1.2 in the mixed solution, heat it in a water bath at 60°C, and react for 2h to make the nitrile group on the surface of the carbon felt loaded with polyacrylonitrile undergo amidoximation reaction. After the reaction, wash the carbon felt with deionized water for multiple times to remove the impurity ions remaining on the surface of the carbon felt, put the cleaned carbon felt into an oven, the oven temperature is 60°C, and the drying time is 12h. After drying, the carbon felt electrode material loaded with amidoxime is obtained.
[0065] Step 2, preparing a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups.
[0066] Step 2.1, measure 200 mL of deionized water, weigh 8 g of sodium hydroxide and dissolve it in 200 mL of deionized water to prepare a sodium hydroxide solution.
[0067] Step 2.2, immersing the carbon felt electrode material loaded with amidoxime in a sodium hydroxide solution, heating in a water bath at 60°C for 15 minutes, and allowing the nitrile groups on the surface of the carbon felt to undergo alkaline hydrolysis. After the reaction, the carbon felt is washed multiple times with deionized water to remove residual impurity ions on the surface of the carbon felt. The washed carbon felt is placed in an oven at 60°C for 12 hours to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups, and carboxyl groups.
[0068] Comparative Example 2
[0069] A method for preparing an amidoxime-loaded carbon felt electrode material comprises the following steps:
[0070] Step 1, preparing a carbon felt electrode material loaded with amidoxime.
[0071] Step 1.1, first cut the carbon felt into 3cm×3cm square pieces, use deionized water to ultrasonically clean the cut carbon felt for 10 minutes to remove soluble impurities on the surface of the carbon felt, use 2% dilute nitric acid to ultrasonically clean the carbon felt for 10 minutes to remove oxides on the surface of the carbon felt, use deionized water to ultrasonically clean the carbon felt again for 10 minutes to remove residual dilute nitric acid, then use anhydrous ethanol to ultrasonically clean the carbon felt for 10 minutes to remove organic impurities on the surface of the carbon felt, then use deionized water to ultrasonically clean the carbon felt for 10 minutes, and then put it into an oven at 60°C to thoroughly dry the carbon felt to prepare bare carbon felt.
[0072] Step 1.2, 10g of polyacrylonitrile powder and 200mL of N,N-dimethylformamide were mixed and stirred for 24h to obtain a polyacrylonitrile coating liquid, the bare carbon felt prepared in step 1.1 was immersed in the coating liquid, ultrasonicated for 10min, so that the coating liquid was evenly coated on the surface of the carbon felt, and after coating, it was placed in an oven at 60°C for 12h to obtain a carbon felt loaded with polyacrylonitrile after drying.
[0073] Step 1.3, measure 150mL of deionized water, weigh 3g of hydroxylamine hydrochloride and 3g of sodium carbonate, mix and dissolve hydroxylamine hydrochloride and sodium carbonate in 150ml of deionized water to obtain a mixed solution. Immerse the carbon felt loaded with polyacrylonitrile obtained in step 1.2 in the mixed solution, heat it in a water bath at 60°C, and react for 2h to make the nitrile group on the surface of the carbon felt loaded with polyacrylonitrile undergo amidoximation reaction. After the reaction, wash the carbon felt with deionized water for multiple times to remove the impurity ions remaining on the surface of the carbon felt, put the cleaned carbon felt into an oven, the oven temperature is 60°C, and the drying time is 12h. After drying, the carbon felt electrode material loaded with amidoxime is obtained.
[0074] The present invention has carried out the following tests to characterize the performance:
[0075] Test 1: Cu 2+ Comparative experiment on electrodeposition effect.
[0076] Measure 50mL of Cu 2+ A CuSO4 solution with a concentration of 100ppm was subjected to an asymmetric alternating current with a frequency of 400HZ, a high potential of +5V for 20% of the time, a low potential of -10V for 80% of the time, and the carbon felt electrode material loaded with amidoxime in Comparative Example 2 and the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups in Comparative Example 1 were used as working electrodes, and a bare carbon felt electrode was used as a counter electrode to conduct an electrodeposition experiment on the CuSO4 solution. A heated constant temperature magnetic stirrer was used to stir the solution, the solution temperature was 25°C, and the speed of the magnetic stirrer was 500r / min.
[0077] When the electrodeposition experiment was carried out for 10min, 20min, 30min, 40min, 50min, 60min, 90min, 120min, and 180min, a 100μL pipette was used to take samples, and the sample solution was diluted to 10mL with 1% HNO3. The sample concentration was measured using an inductively coupled plasma spectrometer, and the working electrode was calculated to determine the concentration of Cu at each time point. 2+ The electrodeposition recovery rate is as follows: Figure 3 shown.
[0078] Test 2: Comparative experiment on the electrocatalytic degradation of methylene blue by carbon felt electrode materials loaded with copper oxide at different voltages.
[0079] The copper oxide-loaded carbon felt electrode material in Example 1 was made into a working electrode. 50 mL of a mixed solution containing methylene blue and sodium sulfate was measured, wherein the concentration of methylene blue was 100 ppm and the concentration of Na2SO4 was 0.1 mol / L. The working electrode was used as the anode and the platinum electrode was used as the cathode. Direct current was used, and the voltages were 10 V, 8 V, 6 V, 4 V, and 2 V, respectively. A heating constant temperature magnetic stirrer was used to stir the mixed solution, and the temperature of the mixed solution was maintained at 25° C. The speed of the magnetic stirrer was 500 r / min.
[0080] At 10min, 20min, 30min, 40min, 50min, and 60min of the experiment, a 100μL pipette was used to take samples, and the sample solution was diluted to 10mL with deionized water. The sample concentration was measured using an ultraviolet spectrophotometer, and the electrocatalytic efficiency of the copper oxide-loaded carbon felt electrode material for methylene blue and the degradation rate of methylene blue at each time point under different voltages were calculated. The results are as follows: Figure 4 shown.
[0081] Test 3: Comparative experiment on the electrocatalytic degradation of methylene blue by carbon felt electrode material loaded with copper oxide at different initial concentrations of methylene blue.
[0082] The copper oxide-loaded carbon felt electrode material in Example 1 was made into a working electrode. Methylene blue trihydrate, Na2SO4 and deionized water were used to prepare mixed solutions with methylene blue concentrations of 100ppm, 80ppm, 60ppm, 40ppm, 20ppm and 10ppm, and Na2SO4 concentrations of 0.1mol / L, respectively. 50mL of the mixed solutions with different initial methylene blue concentrations were measured, respectively, and the working electrode was used as the anode, the platinum electrode was used as the cathode, direct current was used, the voltage was 10V, and the mixed solution was stirred using a heating constant temperature magnetic stirrer, the temperature of the mixed solution was maintained at 25°C, and the speed of the magnetic stirrer was 500r / min.
[0083] At 10min, 20min, 30min, 40min, 50min, and 60min of the experiment, a 100μL pipette was used to take samples, and the sample solution was diluted to 10mL with deionized water. The sample concentration was measured using an ultraviolet spectrophotometer, and the electrocatalytic efficiency of the copper oxide-loaded carbon felt electrode for methylene blue and the degradation rate of methylene blue at each time point in the mixed solution with different initial methylene blue concentrations were calculated. The results are shown in Figure 2. Figure 5 shown.
[0084] Test results:
[0085] Figure 1The present invention provides a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 at different magnifications. a is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; b is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; c is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm; d is a scanning electron microscope image of a carbon felt electrode material loaded with copper oxide at a scale of 200 μm.
[0086] like Figure 1 As shown, the scanning electron microscope images in Figures a to d show that the copper-containing oxides are tightly loaded on the carbon fibers of the carbon felt, and the tightly arranged structure of the copper-containing oxides forms a larger specific surface area on the surface of the carbon felt electrode material loaded with the copper-containing oxides, which is beneficial to the electrocatalytic degradation of the carbon felt electrode material loaded with the copper-containing oxides.
[0087] Figure 2 This is an XRD image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 provided by the present invention.
[0088] Figure 3 This is an EDS image of a carbon felt electrode material loaded with copper oxide prepared in Example 1 provided by the present invention. Specifically, Table 1 is a statistical table of EDS characterization results.
[0089] Table 1 EDS characterization results statistics
[0090] element Mass % Surface atomic concentration% C 18.39 42.70 O 16.47 28.71 Cu 65.14 28.59 total 100.00 100.00
[0091] Combination Figure 2 , Figure 3 As shown in Table 1, after the high-temperature oxidation step, the surface of the carbon felt is loaded with a mixture of copper oxide and cuprous oxide, which indicates that the preparation method of the present invention can prepare a carbon felt electrode material loaded with copper oxide.
[0092] Figure 4 The present invention provides Cu 2+ The test data statistics of the electrodeposition effect comparison experiment. (a) is the effect of different working electrodes on Cu at different time points. 2+ (a) is a comparative statistical chart of the electrodeposition recovery rates of different working electrodes for Cu2+; (b) is a comparative statistical chart of the maximum electrodeposition recovery rates of different working electrodes for Cu2+.
[0093] See also Figure 4In the figure, ACF refers to the carbon felt electrode material loaded with amidoxime, and MACF refers to the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups. As can be seen from Figure (a), the electrodeposition speed of the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups is significantly faster than that of the carbon felt electrode material loaded with amidoxime. The time required for the electrodeposition efficiency of the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups to reach 99.00% is only 60 to 90 minutes, while the carbon felt electrode material loaded with amidoxime requires 90 to 120 minutes. It can also be seen from Figure (b) that the electrodeposition efficiency of the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups is 99.00%. 2+ The recovery rate is the highest, reaching 99.99%.
[0094] The above comparison shows that compared with the carbon felt electrode material loaded with amidoxime, the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups has better Cu 2+ The electrodeposition effect of Cu can be achieved by alkaline hydrolysis of carbon felt electrode materials loaded with amidoxime to obtain modified carbon felt electrode materials containing amidoxime groups, amide groups and carboxyl groups. 2+ The purpose of improving the electrodeposition effect.
[0095] Figure 5 The present invention provides a statistical graph of test data of a comparative experiment on the electrocatalytic degradation of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages. (a) is a statistical comparison of the degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages at different time points; (b) is a statistical comparison of the maximum degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different voltages.
[0096] See also Figure 5 As can be seen from Figures (a) and (b), with the increase of voltage, the rate of electrocatalytic degradation of methylene blue by the copper oxide-loaded carbon felt electrode material also accelerates, and under the action of a voltage of 10 V, the degradation rate of methylene blue can be close to 60% after 60 minutes.
[0097] This is mainly because the greater the voltage, the faster the rate of generating ·OH radicals on the surface of the copper oxide-loaded carbon felt electrode material will be, thereby generating more ·OH radicals to oxidatively degrade methylene blue.
[0098] Figure 6The present invention provides a statistical graph of test data of a comparative experiment on the electrocatalytic degradation of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations. (a) is a statistical comparison graph of the degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations at different time points; (b) is a statistical comparison graph of the maximum degradation rate of methylene blue by a carbon felt electrode material loaded with copper oxide at different initial methylene blue concentrations.
[0099] from Figure 6 It can be seen that in Figure (a), as the initial concentration of methylene blue increases, the degradation rate of methylene blue by electrocatalytic degradation of the carbon felt electrode material loaded with copper oxide gradually decreases. According to Figure (b), when the initial concentration of methylene blue is 10ppm, the degradation rate of methylene blue by electrocatalytic degradation of the carbon felt electrode material loaded with copper oxide is optimal, and the degradation rate is greater than 90%; when the initial concentration of methylene blue is 100ppm, the degradation rate of methylene blue by electrocatalytic degradation of the carbon felt electrode material loaded with copper oxide can still be close to 60%.
[0100] This is because under the conditions of the same applied voltage and the same Na2SO4 concentration, the number of ·OH radicals produced per unit time is the same, and the same number of ·OH radicals degrades the same amount of methylene blue per unit time. Therefore, the higher the initial concentration of methylene blue, the lower the degradation rate.
[0101] In summary, the above test results show that the carbon felt electrode material loaded with copper oxides prepared by the preparation method of the present invention can have a good electrocatalytic degradation effect on the dye solution, indicating that the carbon felt electrode material loaded with copper oxides can be used to degrade dye wastewater.
[0102] In addition, the above test results show that it is feasible to obtain the copper element required in the copper-containing oxide by electroplating the copper-containing wastewater. Compared with the carbon felt electrode material loaded with amidoxime, the modified carbon felt electrode material containing amidoxime, amide and carboxyl groups prepared by the preparation method of the present invention can improve the recovery rate of copper elements in copper-containing wastewater, thereby reducing the cost of obtaining copper elements, and further reducing the preparation cost of the carbon felt electrode material loaded with copper oxide, so as to facilitate the promotion and application of the carbon felt electrode material loaded with copper oxide in the electrocatalytic degradation of dye wastewater.
[0103] The above description is only a preferred embodiment of the present invention, and the above specific embodiment is not intended to limit the present invention. Various deformations and modifications may occur within the scope of the technical concept of the present invention, and any modification, modification or equivalent replacement made by a person of ordinary skill in the art based on the above description shall fall within the scope of protection of the present invention.
Claims
1. A method for preparing a carbon felt electrode material loaded with copper oxide, characterized in that: The following steps are involved: The carbon felt electrode material loaded with amidoxime groups is subjected to a hydrolysis reaction in an alkaline solution, and the nitrile groups of polyacrylonitrile are hydrolyzed into amide groups and carboxyl groups, so as to obtain a modified carbon felt electrode material containing amidoxime groups, amide groups and carboxyl groups; Using modified carbon felt electrode materials containing amidoxime, amide and carboxyl groups as working electrodes, a double electrode system was used to perform electrodeposition treatment on copper-containing wastewater to obtain copper-containing carbon felt electrode materials. performing an oxidation reaction on the copper-containing carbon felt electrode material, oxidizing copper into copper-containing oxides, and obtaining a carbon felt electrode material loaded with copper-containing oxides; Wherein, the copper-containing oxide is a mixture of cuprous oxide and cupric oxide.
2. The method for preparing the copper oxide-loaded carbon felt electrode material according to claim 1, characterized in that: The alkaline solution is at least one of a sodium hydroxide solution and a potassium hydroxide solution, and the concentration of the alkaline solution is 0.5 mol / L to 1.5 mol / L.
3. The method for preparing the copper oxide-loaded carbon felt electrode material according to claim 2, characterized in that: The reaction temperature of the hydrolysis reaction is 50°C to 70°C.
4. The method for preparing the copper oxide-loaded carbon felt electrode material according to claim 1, characterized in that: The method for preparing the amidoxime-loaded carbon felt electrode material comprises the following steps: The carbon felt is immersed in a polyacrylonitrile solution and subjected to ultrasonic treatment so that the polyacrylonitrile is uniformly loaded on the carbon felt, thereby obtaining the carbon felt loaded with polyacrylonitrile; The carbon felt loaded with polyacrylonitrile is immersed in a hydroxylamine hydrochloride-sodium carbonate solution to make polyacrylonitrile and hydroxylamine hydrochloride undergo amidoxime reaction, thereby obtaining the carbon felt electrode material loaded with amidoxime.
5. The method for preparing a carbon felt electrode material loaded with copper oxide according to claim 4, characterized in that: The polyacrylonitrile solution is prepared by dissolving polyacrylonitrile in N,N-dimethylformamide, and the mass concentration of the polyacrylonitrile solution is 0.04 g / mL to 0.06 g / mL.
6. The method for preparing a carbon felt electrode material loaded with copper oxide according to claim 4, characterized in that: The hydroxylamine hydrochloride-sodium carbonate solution is prepared by dissolving hydroxylamine hydrochloride and sodium carbonate in water, wherein the mass ratio of the hydroxylamine hydrochloride to the sodium carbonate is 1:1, and the mass concentrations of the hydroxylamine hydrochloride and the sodium carbonate in the hydroxylamine hydrochloride-sodium carbonate solution are 0.03 g / mL to 0.05 g / mL.
7. The method for preparing a copper oxide-loaded carbon felt electrode material according to claim 1, characterized in that: The temperature of the oxidation reaction is 500°C to 600°C.
8. The method for preparing a copper oxide-loaded carbon felt electrode material according to claim 1, characterized in that: The metal element in the copper-containing wastewater is copper.
9. A carbon felt electrode material loaded with copper oxide, characterized in that: The copper oxide-loaded carbon felt electrode material is prepared by the method for preparing the copper oxide-loaded carbon felt electrode material according to any one of claims 1 to 8.
10. Use of the copper oxide-loaded carbon felt electrode material according to claim 9 as an electrode in degrading dye wastewater.
Citation Information
Patent Citations
Preparation method and application of titanium-based copper oxide doped tin antimony oxide electrode
CN112110523A